Fatigue crack growth simulation in adhesively bonded composite joints. Issue 7 (21st December 2018) - Tserpes, Konstantinos; Floros, Ioannis
Abstract: A numerical model has been developed for simulating fatigue crack growth (debonding) in adhesively bonded composite joints subjected to mode‐I, mode‐II, and mixed‐mode I + II loading conditions. The model employs a cohesive zone model described by a modified bilinear traction‐separation law. Fatigue damage in the composite adherends is not considered in the model. To account for crack divergence and reduce sensitivity of numerical results on mesh density, a crack front detection algorithm based on the effective element's length was employed. The model is implemented as a user‐defined subroutine (UMAT) in the commercial FE code LS‐DYNA. The model's input parameters, in the form of a modified Paris law, and the validation data were obtained from experimental tests conducted by the authors. It was found that the model is able to successfully simulate crack growth in the regime of the experimental data.